Development of Amplification Test-Systems for Tularemia Agent Detection - N. A. Osina; A. M. Senichkina; T. V. Bugorkova; S. A. Shcherbakova (Проблемы особо опасных инфекций, 2015)
Developed is the method for tularemia microbe DNA detection using PCR with electrophoretic and hybridization-fluorescent registration of results. iglBC genes have been chosen as DNA-matrixes, being species-specific ones for tularemia agent. Based on the results obtained constructed have been preparations for tularemia microbe DNA detection in biological material and environmental samples applying PCR with electrophoretic registration of results and real-time PCR: “Gene Francisella tularensis - REP” and “Gene Francisella tularensis RHF”, respectively. Identified are the package contents to be included into the test-systems. Sensitivity and specificity of the designed panels are validated through investigations of tularemia agent bacterial emulsions and suspensions from small mammals’ organs, from ticks, fleas and mosquitoes, as well as through studies of soil and surface water samples, sputum and human blood probes, experimentally contaminated with tularemia agent. Test-systems demonstrate high sensitivity (1·103 microbe cells/ml) and specificity (100 %), irrespective of the type of test material.